2015
DOI: 10.1155/2015/360973
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of CXCR3+CD4+CD25+Foxp3+ Regulatory T Cells in Renal Ischemia‐Reperfusion Injury

Abstract: Regulatory T cells (Tregs) suppress excessive immune responses and are potential therapeutic targets in autoimmune disease and organ transplantation rejection. However, their role in renal ischemia-reperfusion injury (IRI) is unclear. Levels of Tregs and expression of CXCR3 in Tregs were analyzed to investigate their function in the early phase of renal IRI. Mice were randomly divided into Sham, IRI, and anti-CD25 (PC61) + IRI groups. The PC61 + IRI group was established by i.p. injection of PC61 monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Previous studies have demonstrated that human peripheral CD4 + CD25 + Tregs can be accurately identified and purified using surface expression of CD127, as an alternative to the transcription factor FOXP3 (38)(39)(40)(41)(42)(43) + Tregs in the current study. A number of therapeutic approaches are aimed at inhibiting immune suppression within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have demonstrated that human peripheral CD4 + CD25 + Tregs can be accurately identified and purified using surface expression of CD127, as an alternative to the transcription factor FOXP3 (38)(39)(40)(41)(42)(43) + Tregs in the current study. A number of therapeutic approaches are aimed at inhibiting immune suppression within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 68%
“…low cells [64]. Similar to what occurs in humans, the use of this marker could also be controversial, as there is a subpopulation of activated CD4 1…”
Section: Cd25mentioning
confidence: 99%
“…Tregs were observed to infiltrate in ischaemic-reperfused kidneys, which modulated pro-inflammatory cytokines production by other immune cells [14-17]. IL-10-producing Tregs were involved because the adoptive transfer of IL-10-deficient Tregs into Rag-1 knockout mice failed to recover renal function [15].…”
Section: Treg-mediated Repair At Multiple Tissuesmentioning
confidence: 99%